Microbiological characterization of Delftia acidovorans clinical isolates from patients in an intensive care unit in Brazil - Camargo, Carlos Henrique; Ferreira, Adriano Martison [UNESP]; Javaroni, Edvaldo; Reis, Brígida Aparecida Rosa; Bueno, Maria Fernanda Campagnari; Francisco, Gabriela Rodrigues; Gallo, Juliana Failde; de Oliveira Garcia, Doroti (Elsevier, 2014)
Delftia acidovorans is an opportunistic agent in several types of infections, both in immunocompromised and immune-competent individuals; its resistance to aminoglycosides and polymyxin, choice drugs for empirical treatment of Gram-negative infections, is remarkable. We report the antimicrobial susceptibility and the genetic relatedness of 24 D. acidovorans strains recovered from tracheal aspirates of 21 adult inpatients hospitalized in an intensive care unit at a Brazilian hospital, from 2012 to 2013. All of the isolates were recovered as pure cultures and in counts above 1,000,000 CFU/mL. None of them were susceptible to polymyxin B, amikacin, gentamicin, or tobramycin; quinolones and trimethoprim-sulfamethoxazole presented varied activities against the isolates, while β-lactam resistance was not detected. Four clusters were verified in pulsed-field gel electrophoresis analysis, and a major pulsotype comprised 10 strains. A possible, but undetermined common source, can be responsible for this strain dissemination, underscoring the need of reinforcing the adherence to disinfection and infection control standard techniques.
Keywords: Cross infection; Delftia acidovorans; Drug resistance; Electrophoresis; Gel; Microbial sensitivity tests; Molecular epidemiology; Pulsed-field